2018
DOI: 10.3390/mi9070316
|View full text |Cite
|
Sign up to set email alerts
|

Erbium Luminescence Centres in Single- and Nano-Crystalline Diamond—Effects of Ion Implantation Fluence and Thermal Annealing

Abstract: We present a fundamental study of the erbium luminescence centres in single- and nano-crystalline (NCD) diamonds. Both diamond forms were doped with Er using ion implantation with the energy of 190 keV at fluences up to 5 × 1015 ions·cm−2, followed by annealing at controllable temperature in Ar atmosphere or vacuum to enhance the near infrared photoluminescence. The Rutherford Backscattering Spectrometry showed that Er concentration maximum determined for NCD films is slightly shifted to the depth with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…A dense and highly uniform NCD layer was obtained with a maximum grain size of about 100 nm. The Raman spectrum and its deconvolution results according to [54] are displayed in Figure 5c. A sharp and intense diamond peak is located at 1333.5 cm −1 , demonstrating good diamond quality.…”
Section: Raman Spectra and Residual Stressmentioning
confidence: 99%
“…A dense and highly uniform NCD layer was obtained with a maximum grain size of about 100 nm. The Raman spectrum and its deconvolution results according to [54] are displayed in Figure 5c. A sharp and intense diamond peak is located at 1333.5 cm −1 , demonstrating good diamond quality.…”
Section: Raman Spectra and Residual Stressmentioning
confidence: 99%
“…The experimental research on Er-doped single-and nano-crystalline diamond was reported by our group in several publications. 60,95,99,100 4.4.1. Er-doped diamond -theoretical results.…”
Section: Er-doped Diamondmentioning
confidence: 99%
“…A number of other defects in diamond, such nickel‐related color center, [ 186–190 ] chromium‐related centers, [ 30,190 ] and rear‐earth elements [ 191 ] were also considered as candidates for single‐photonic emitters and for photonics in general. From this variety we will touch here only luminescent properties of GeV centers and rear‐earths in diamond.…”
Section: Emerging Color Centers In Diamondmentioning
confidence: 99%